1994
DOI: 10.1002/mus.880170303
|View full text |Cite
|
Sign up to set email alerts
|

Median nerve sensory responses evoked by tactile stimulation of the finger proximal and distal phalanx in normal subjects

Abstract: We compared the characteristics of near-nerve recorded sensory potentials elicited in response to electrical stimulation of digital nerves versus tactile stimulation of the digital skin in 17 healthy subjects with a mean age of 26 years. We also calculated the density of Meissner's corpuscles in the distal and proximal phalanx of digit III of 6 males who had suffered a violent death, but were free from diseases of the peripheral nerve system. Responses to tactile stimulation had a longer latency and lower ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…12 According to a classic microneurographic study by Johansson and Vallbo, 6 the density of rapidly adapting Meissner units was highest at the fingertip, moderate at the finger base, and lowest at the thenar eminence. In relative terms, the density of Meissner corpuscles was 45% lower at PP than at FT, and 82% lower at Pm than at FT. 6 Recently, in histological studies Caruso et al 5 found that the density of Meissner corpuscles was considerably greater in the distal phalanx than in the proximal phalanx. The Pacinian corpuscles were more evenly distributed, although there was a more variable and lower density at the Pm than at the FT and PP.…”
Section: Sources Of Errormentioning
confidence: 98%
“…12 According to a classic microneurographic study by Johansson and Vallbo, 6 the density of rapidly adapting Meissner units was highest at the fingertip, moderate at the finger base, and lowest at the thenar eminence. In relative terms, the density of Meissner corpuscles was 45% lower at PP than at FT, and 82% lower at Pm than at FT. 6 Recently, in histological studies Caruso et al 5 found that the density of Meissner corpuscles was considerably greater in the distal phalanx than in the proximal phalanx. The Pacinian corpuscles were more evenly distributed, although there was a more variable and lower density at the Pm than at the FT and PP.…”
Section: Sources Of Errormentioning
confidence: 98%
“…In humans, RA receptors are concentrated at the distal ends of digits I-III (Johansson, 1978;Johansson and Vallbo, 1979), where tactile acuity is greatest (Caruso et al, 1994). MC densities range from 5.4 mm Ϫ2 in the thenar eminence to 33 Ϯ 13 and 24 Ϯ 10 mm Ϫ2 in the pads of digits III and V, respectively (Bolton et al, 1966;Nolano et al, 2003).…”
Section: Distribution and Adaptive Significance Of Meissner Corpusclesmentioning
confidence: 99%
“…As in previous studies 6,7,11,12,28 the tactile CSAPs were polyphasic in shape due to asynchronous firing, and the peak-to-peak amplitudes could therefore differ if the indentation velocities caused changes in synchronization of firing rather than in the number of activated fibers. In order to partially compensate for this possibility we rectified and integrated the responses.…”
Section: Discussionmentioning
confidence: 83%
“…20 The higher maximal SNCVs at T400 than at T100 stimulation was in accordance with previous studies. 11,12,28 The different SNCVs strongly indicated that different populations of receptors reacted to the different indentation velocities. It seems likely that receptors were activated at T400 stimulation which were not activated at T100 stimulation.…”
Section: Activation Of Different Mechanoreceptors By Differ-mentioning
confidence: 97%